BEST PRATICE MENINGKATKAN KEMAMPUAN MENULIS TEKS CERPEN SISWA KELAS IX SMP NEGERI 15 TAMBUSAI UTARA DENGAN MODEL PROBLEM BASED LEARNING MELALUI STRATEGI COPY THE MASTER - Fitria Mandasari (sarasvati, 2022)
The Problem Based Learning using Copy the Master strategy through Audio Visual media (short films) can be used to improve the ability to write short stories because these models, strategies, and media provide students with idioms to find and start short story writing activities. The activity of writing short stories in the process of good practice by author has shown an increase in the ability to write short stories. The improvement in the ability to write short stories made by students can be seen from the increase in the enthusiastic learning process and the work in the form of short stories.